Application Of Management Accounting System To Product Quality Control At Pt Bio Maraja Nusantara - Deswita Deswita; Ansyarif Khalid; Nurhidayah Nurhidayah (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to determine the application of the management accounting system to product quality control at PT Bio Maraja Nusantara. This study uses a qualitative descriptive method, data is collected by observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, through the stages of data collection, data reduction, data presentation, and conclusion drawn. The results of the study show that PT Bio Maraja Nusantara implements a management accounting system effectively, focusing on quality control from raw materials to finished products. This system ensures that every stage of production adheres to strict quality standards, as well as motivates employees through a system of quality- and quantity-based incentives. Although the company has implemented this system well, the main recommendation is to maintain and continuously improve the management accounting system so that product quality control remains optimal.